The Reception of Classical Latin Literature in Early Modern Philosophy: the case of Ovid and Spinoza (Revista Archai, 2018)
Although the works of the authors of the Golden Age of Latin Literature play an important formative role for Early Modern philosophers, their influence in Early Modern thought is, nowadays, rarely studied. Trying to bring this topic to light once again and following the seminal works of Kajanto (1979), Proietti (1985) and Akkerman (1985), I will target Spinoza’s Latin sources in order to analyze their place in his philosophy. On those grounds, I will offer an overview of the problems of the reception of classical literature in Early Modernity and then dwell on the particular case of Ovid and Spinoza. The present paper will argue that although Spinoza’s references to Ovid fill a rhetorical purpose as suggested by the existing literature, these mentions have a prior philosophical motivation. That is, the references in the Ethics are not merely illustrative; instead, they indicate that Spinoza acknowledges Ovid’s beliefs about human experiences and deliberately elaborates on Ovid’s view to construct and defend his own theses. To this end, the paper will analyze some citations mapped by Proietti (1985) and add a new one in an attempt to enlarge the list of places and topics that merit further investigation. To conclude, I will point out how the references to Ovid are part of Spinoza’s own defense of the powers of imagination.